Peningkatan Keterampilan Menulis Argumentasi Siswa Kelas X SMK N 1 Batusangkar dengan Pendekatan Kontekstual - A., Darma Yulia; R., Syahrul; Ratna, Ellya (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The problem in this research is the writing skill of the argumentative essay of Grade X students of SMK N 1 Batusangkar was low, so it needs a strategy that can improve the writing skills of argumentative essay. This research is a classroom action research by using descriptive method. The data described in a qualitative research based on observation sheets, field notes, and test. For the studentsâ€™ achievement, data obtained from the performance tests by writing argumentative essay. This study was conducted in two cycles, each cycle had two meetings. The procedure of every cycle consists of four steps, namely (1) planning, (2) actions, (3) observation, and (4) reflection. The subjects were students of class X. K.1 of SMK N 1 Batusangkar. They were 34 students. Based on the description and analysis of the finding, some conclusions can be drawn: First, the process of learning by using Contextual Approach in teaching writing of argumentative essay ran well.Â  Second, the average writing skills test in writing argument essay by using Contextual Approach increased from 23.53% in first cycle to 94.11% in the second cycle.